LIGHTS, CAMERA AND PROPAGANDA: BOLLYWOOD MOVIES UNDER THE PRESSURE TO MEET POLITICAL AGENDA; WITH SPECIAL REFERENCE TO THE CHANGING DIMENSIONS OF SATYAJIT RAY’S MOVIES - Chowdhury, Shubhajit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Movies are the mirror of the society, and based on the movies people can get into the reality of the society. The motif of this paper is to question the relevance of this statement, based on several instances taken from Satyajit Ray’s movies to our contemporary movies. The reality is that after the media, movies have also become politicized, politicians use movies to promote their political propaganda and stimulate the mind of the audience. Starting from Satyajit Ray, along with the masterpieces, how his movies were politicized to promote the Nehruvian ideologies to the global audience. How Ray’s characters were prototypes of the Nehruvian ideologies. How Ray presents both poverty and ambition in movies but focuses more on his character’s ambitions rendering that with Nehruvian ambition for modern India. This hereditary politicization of movies has continued till the present, and in the present scenario, the movies are fabricating the reality at such a level that, they appear more real than the reality to their audience. All because it stimulates the perspectives of the audience towards political propaganda. This paper will focus more on decoding the politicization of Satyajit Ray’s earlier movies. While doing that this paper will decode one movie from the contemporary era, to prove that politicization in Bollywood is a traditional practice.